VALIDITAS PENGEMBANGAN LKPD BERBASIS PBL BERMUATAN ISLAMI PADA MATERI TRIGONOMETRI KELAS X - nurus salamah (LPPM Universitas KH.A.Wahab Hasbullah Jombang, 2021)
Mathematics is a basic science that trains students' abilities to get used to solving a problem that is around them. But in reality it shows that in the learning process, the learning media that are used have not trained students in conducting an invention and students are less active in the learning process. This study aims to produce learning media in the form of Islamic Learning Based Problem Based Learning Worksheet based on Trigonometry material. This research method is Research and Development with the ADDIE development model which has been adapted into the ADD stage. The steps taken are only stage 1 to stage 7, namely analysis, design and development. Validation results from lecturers get an average yield of 81.2% with valid criteria and validation results from educators get an average result of 86.4% with valid criteria. The average validation results by the two validators were 83.8% with valid criteria.